Management of Intussusception in the Pediatric Emergency Department: Risk Factors for Recurrence. Issue 4 (April 2020) - Vo, Andrea; Levin, Terry L.; Taragin, Benjamin; Khine, Hnin
Abstract : Background: The standard treatment for intussusception is air reduction enema (ARE) with inpatient observation for 24 to 48 hours to monitor for recurrence. More recent but limited observations suggest that patients who have undergone successful ARE can safely be discharged after 4 to 6 hours of observation. Our primary objective was to identify risk factors associated with early recurrence. Our secondary objectives included validating risk criteria from prior studies and identifying risk factors for ARE failures. Design/Methods: A retrospective cohort study of children discharged from a large urban quaternary hospital with a final diagnosis of intussusception ( International Classification of Diseases, Ninth Revision, code 560.0) or who underwent ARE from 2005 to 2015 was identified. Demographic data, radiology images, and clinical course were recorded. Repeat visits, cases with incomplete medical records, and those with incorrect diagnoses were excluded. Results: A total of 250 cases were identified. Two hundred cases were included for analysis. Fifty were excluded. Of the 163 who had successful reduction with ARE, 22 patients (13.5%) recurred, and 12 (7.3%) recurred within 48 hours. Fever (odds ratio, 4.25; P = 0.04; 95% confidence interval, 1.04–17.3) and female sex (odds ratio, 7.94; P = 0.01; 95% confidence interval, 1.82–34.6) were independently associated with early recurrence. No radiologic features were associated with early recurrence. Conclusions: Early recurrence after successful ARE was low, although more frequent in girls and in those with fever over 100.4°F. We therefore advocate for prospective studies to validate these risk criteria to identify patients who are at low risk for early recurrence and may qualify for early discharge from the emergency department.